Representasi Adegan Kekerasan dalam Tayangan Komedi Televisi (Analisis Semiotika Terhadap Program Opera Van Java di Trans7) - Endah Fantini (Majalah Ilmiah Bijak, 2018)
Opera Van Java (OVJ) Television program on Trans7 earns a high rating and share in a relatively short time. This is a new phenomenon in the category of comedy that shows a television program in Indonesia can be successful. This event received much praise, so the OVJ included a comedy that received great public attention. The silly story presented by OVJ is very funny and appealing to all walks of life.Trans7's communications management on this television comedy program has demonstrated professional work in managing comedy programs. This is done by building the synergy / performance of all the crew, communicating creative ideas and ideas, equating perceptions, packing messages and impressions. This process creates an OVJ program that appeals to the audience and can convey messages to all walks of life and age.The Trans7 OVJ program got the highest rating and share of the comedy version according to AGB Nielsen measurement by Audiences Meansurement version. This assessment is very influential, because the OVJ program is a phenomenal comedy that will increase advertising revenue as a source of income Trans7 television stations.Creativity in communication management Opera Van Java (OVJ) is packaged in such a way that it is always interesting to watch on every episode. Researchers found and saw great creativity in the OVJ program. The conclusion is that good communication management in managing television comedy programs is essential to improve the rating and share of the program.